Implementasi Kurikulum Merdeka Belajar Pada Sekolah Dasar Mempengaruhi Pada Hasil Evaluasi Belajar Peserta Didik - Pingky Sukma Melati (Proceedings Series of Educational Studies, 2023)
Abstract: The independent learning curriculum in elementary schools is a curriculum approach that aims to give freedom to students in determining the course of learning, while taking into account the competency standards that must be achieved. The independent learning curriculum in elementary schools involves students in the learning process and provides opportunities for them to determine the course of learning. This is done by giving students the freedom to choose the topics they want to study, the learning methods that are most suitable for them, and to follow programs that suit their interests and needs. This research method uses data collection in the form of observation, interviews and documentation. The results of the analysis obtained data on the effectiveness of implementing the independent learning curriculum at SDN Jambearjo 01. Data was obtained that schools were still trying to adapt to the new curriculum so that the implementation of the independent curriculum had not been fully achieved. One aspect that needs to be readjusted by schools is the aspect of exams and learning. The exam or assessment aspect has specific criteria, namely adjusting the achievement of students and this is a point of concern for the school.Keywords: Curriculum, Evaluation, StudentsAbstrak: Kurikulum merdeka belajar pada sekolah dasar adalah suatu pendekatan kurikulum yang bertujuan untuk memberikan kebebasan kepada siswa dalam menentukan jalannya belajar, dengan tetap memperhatikan standar kompetensi yang harus dicapai. Kurikulum merdeka belajar pada SD melibatkan siswa dalam proses pembelajaran dan memberikan kesempatan kepada mereka untuk menentukan jalannya belajar. Hal ini dilakukan dengan memberikan kebebasan kepada siswa untuk memilih topik yang ingin dipelajari, metode pembelajaran yang paling cocok untuk mereka, dan mengikuti program yang sesuai dengan minat dan kebutuhan mereka. Metode penelitian ini menggunakan pengumpulan data berupa observasi, wawancara dan dokumentasi. Hasil analisis diperoleh data keefektifan penerapan kurikulum merdeka belajar pada SDN Jambearjo 01. Diperoleh data bahwa sekolah masih berupaya beradaptasi dengan kurikulum baru sehingga penerapan kurikulum merdeka belum sepenuhnya tercapai. Salah satu aspek yang perlu diadaptasi kembali oleh sekolah ialah aspek ujian serta pembelajaran. Aspek ujian atau penilaian memiliki kriteria spesifik yakni menyesuaikan ketercapaian peserta didik dan hal itu menjadi poin perhatian oleh sekolah.Kata kunci: kurikulum, Merdeka belajar, evaluasi, peserta didik